2015
DOI: 10.1097/igc.0000000000000377
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Analysis With Immunohistochemistry for DNA Mismatch Repair Protein Expression in Synchronous Primary Endometrial and Ovarian Cancers

Abstract: These results suggest that most synchronous primary endometrial ovarian cancers are not hereditary cancers caused by germ line mutations but rather sporadic cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 30 publications
1
27
0
1
Order By: Relevance
“…28 Previous studies are equivocal on the interest to search for LS in case of synchronous endometrial and ovarian tumors. 35 However, these synchronous tumors seem to be more common among LSrelated EC cases.…”
Section: Discussionmentioning
confidence: 99%
“…28 Previous studies are equivocal on the interest to search for LS in case of synchronous endometrial and ovarian tumors. 35 However, these synchronous tumors seem to be more common among LSrelated EC cases.…”
Section: Discussionmentioning
confidence: 99%
“…14 Besides, it has been suggested that most SCEOs are not hereditary cancers caused by germ line mutations, but instead, they are sporadic cancers. 13 So, we still use only histopathologic criteria to differentiate between these 2 entities.…”
Section: Discussionmentioning
confidence: 99%
“…In the future some molecular profiles and genetic changes that present in these tumor may improve the distinction of independent primary tumors. 9 Mean age at diagnosis of women with primary SEOC in our study was 50.9. In contrast, women who develop endometrial or ovarian cancer alone are generally postmenopausal and in the sixth or seventh decade of life.…”
Section: Discussionmentioning
confidence: 67%